Tantangan dan Sumber Daya Inovasi Pendidikan Agama Islam (Madrasah dan Pondok Pesantren) - Bahrudin, Andre; Sirozi, M (LPPM Institut Pendidikan Nusantara Global, 2025)
Islamic education plays a crucial role in shaping the character and personality of the younger generation, particularly through madrasahs and pesantrens. However, in the context of globalization and rapid technological advancement, these institutions face increasingly complex challenges. This study aims to identify the challenges encountered by madrasahs and pesantrens in innovating their educational practices and to analyze the resources that can support this innovation process. Utilizing a qualitative approach, data were collected through interviews with educational administrators, teachers, and students, as well as document analysis related to educational policies. The findings indicate that effective innovation requires synergy among various stakeholders, including the government, society, and educational institutions themselves. Additionally, enhancing teacher capacity and incorporating information technology into the learning process are key to improving the quality of Islamic education in Indonesia.